2014
DOI: 10.5539/elt.v7n5p110
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Portfolio Assessment on EFL Learners’ Reading Comprehension and Motivation

Abstract: This study highlighted the humanistic-transformational perspectives via portfolio assessment which offers a conceptual framework for teaching and assessment. More specifically, it attempted toexplore the effectof portfolioassessmenton EFL learners'reading comprehension ability and motivation in the context of Iran. It adopted the quasi-experimental design comprising the pretest-treatment-posttest paradigm. To achieve the purpose, the researchers collected the triangulated data about the participants. Two class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…The results of research previously which are related to portfolio come from Hosseini and Gabhanci in [9] who show that portfolio assessment has a significant effect in enhancing students' reading experience and motivation, similar to this finding is the finding of a research done by Dewi, Dantes & Marhaeni in [10] in which it is shown that the use of portfolio assessment can increase writing ability in English after verbal ability is controlled.…”
Section: Introductionsupporting
confidence: 74%
“…The results of research previously which are related to portfolio come from Hosseini and Gabhanci in [9] who show that portfolio assessment has a significant effect in enhancing students' reading experience and motivation, similar to this finding is the finding of a research done by Dewi, Dantes & Marhaeni in [10] in which it is shown that the use of portfolio assessment can increase writing ability in English after verbal ability is controlled.…”
Section: Introductionsupporting
confidence: 74%
“…These artefacts are usually subject-specific and diverse in forms. For L2 learning purposes, they can involve written essays, reading logs, multimedia materials, reflections, self-assessment, and peer feedback (e.g., Baturay & Daloğlu, 2010;Farahian & Avarzamani, 2018;Hosseini & Ghabanchi, 2014;Huang & Hung, 2010;Kabilan & Khan, 2012;Sharifi et al, 2017;Thang et al, 2012).…”
Section: Portfolio-based Learning L2 Motivation and Listening Skillmentioning
confidence: 99%
“…As Burner (2014) puts it, "[i]t does not matter how productive PA [portfolio assessment] has proved to be if the students are not motivated" (p. 145). Furthermore, although PoBL has been implemented to promote various L2 abilities, including writing skill (e.g., Aliweh, 2011;Farahian & Avarzamani, 2018;Lam, 2013;Nicolaidou, 2013), speaking skill (e.g., Hung & Huang, 2016), reading skill (e.g., Charvade et al, 2012;Hosseini & Ghabanchi, 2014), and vocabulary learning (e.g., Sharifi et al, 2017), whether and how PoBL can be implemented for teaching L2 listening skill are relatively unknown.…”
Section: Portfolio-based Learning L2 Motivation and Listening Skillmentioning
confidence: 99%
See 1 more Smart Citation
“…More specifically, the use of a portfolio assessment can help teachers to pay attention to the student's development, diagnose learning difficulties experienced by students, find out the students ' needs, interests, etc. This practice in assessing students' achievement is in line with the statement made by Nasution & Suryanto (2008) which highlight the need for assessments to not only focus on the learning outcomes, but also the learning process. In relation to this, Hosseini and Ghabanchi (2014) suggest that one alternative assessment that can be used to show students' activities and various learning strategies is portfolio assessment. Thus, it will not only help teachers who can see the development of students but also the parents.…”
mentioning
confidence: 99%